Technological innovation generating economic results - Libecap, Gary D.; Thursby, Marie C. (Emerald, 2008)
Profiting from technological innovation is a key strategic challenge in technology-intensive industries because it requires not only scientific and engineering expertise but also an understanding of how business and legal factors facilitate commercialization. This volume presents a multidisciplinary view of issues in technology commercialization and entrepreneurship. First, the strategic options available to an innovating firm attempting to commercialize inventions are presented in the context of the legal system and the complementary assets needed for commercialization. Next, the benefits and liabilities associated with multidisciplinary commercialization teams are covered. The chapters on intellectual property include a basic guide to patents, designs, copyrights, trademarks and trade secrets and marks, as well as an analysis of how these mechanisms can be viewed as complements in commercialization. Issues and challenges associated with US laws such as Bayh-Dole are covered. Three chapters cover elements of strategy including industry analysis and strategy, marketing strategy, alliances and other strategies for technology commercialization. The final chapters cover financial issues in commercialization, with a guide to different techniques used in valuing early stage technologies, steps in obtaining venture capital funding, and an analysis of the role of contracts and nondisclosure agreements in licensing of early stage inventions.
Keywords: Technological innovations -- Economic aspects.; Business enterprises -- Finance.; elektronické knihy; electronic books